Sexual abuse within the church : assessment, intervention, and prevention - Rush Burkey, Chris; Braswell, Michael; Whitehead, John T. (New York, NY : Routledge, 2021)
"This book takes a holistic approach by providing insight into the behavior and nature of sex offenders within the church. The text covers various types of sex offenders as well as their criminal propensities and methods of acquiring victims. Warning signs associated with sex crimes within the church are explained as well as security measures and prevention strategies that church leaders and criminal justice professionals can utilize to minimize risk to congregants. Discussion questions and case study scenarios are provided to allow the reader to examine relevant issues and explore a range of potential solutions and interventions. This comprehensive book is intended for criminal justice academicians who teach courses on sex crimes and sex offenders, criminal justice agents (police and investigators), seminary professors and students, and clergy members. It can also assist security teams, church board members, leaders, and teachers in developing intervention and prevention strategies"--
OCLC-licensed vendor bibliographic record.
Keywords: Sex -- Religious aspects -- Christianity; Christians -- Sexual behavior; Sex crimes -- Religious aspects -- Christianity; SOCIAL SCIENCE / Criminology